PERAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN PETANI PADI SAWAH DI DESA BANTAYAN KECAMATAN LUWUK TIMUR - Anggo, Hardi; Djamaluddin, Ismail; Yatim, Hertasning (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Paddy rice is one of the most widely consumed staple foods around the world including the Banggai Regency area. Thus, the role of farmers is very important in farming to maintain the availability of food. Apart from that, the income of farmers is also important in determining the level of welfare of these rice farmers. Thus, this study aims to determine the role of farmer groups and determine the income of paddy rice farmers in Bantayan Village, East Luwuk District, Banggai Regency. The research was conducted from June to August 2023 in Bantayan Village, East Luwuk District, Banggai Regency. The determination of this location was done deliberately with the consideration that Bantayan Village is one of the rice-producing villages. This research uses Likert scale and income analysis methods. The results obtained, namely, the role of farmer groups in disseminating information obtained (73.14%), the provision of facilities and means of production (70.9%), planning activities (75.5%), the application of five farming technologies (70.9%), and cooperation with KUD institutions (88%), which means all the activities of rice paddy farmer groups in the village of Bantayan District East Luwuk classified as very active and high category. In addition, based on the analysis of income from the total income of farmers in Bantayan Village, East Luwuk Subdistrict obtained from the reduction between total revenue (TR) of IDR. 28,656,000 and total costs (TC) of IDR. 2,441,229, then the income (π) = TR - TC is IDR. 26,214,771. thus, rice paddy farming can still be continued to be cultivated because the amount of income obtained is quite high and profitable.